Penilaian Tingkat Kesehatan PT Kawasan Industri Wijayakusuma Semarang Tahun 2019-2023 - Fitriana Ade Suci Rahayu (Politeknik Raflesia Press, 2025)
The purpose of this research is to assess the health level of PT Kawasan Industri Wijayakusuma Semarang from 2019 to 2023, to examine the development of the company's health level before and after the holding, and to identify the strategies implemented to improve the health level of PT Kawasan Industri Wijayakusuma Semarang from 2019 to 2023. This study is categorized as both quantitative and qualitative research. The research sample consists of the financial reports of PT Kawasan Industri Wijayakusuma from 2019 to 2023, and the analytical method used is based on Kepmen 100 of 2002, particularly its financial aspects, and triangulation of data. The results show that in 2019, 2021, 2022, and 2023, the company's health level was categorized as Healthy, while in 2020, it decreased to Fairly Healthy. The effect of the holding on the company's health level can be seen from the stability in its health level after the holding and the increased revenue post-holding. Strategies implemented by PT Kawasan Industri Wijayakusuma to maintain the company's health level include improving infrastructure, monitoring and evaluation, investing in human resources (HR) development, participating in investment forums, and executing Corporate Social and Environmental Responsibility (TJSL) programs.